A healing curve: The poetry of Taqralik Partridge in Inuktitut translation - Henitiuk, Valerie; Mahieu, Marc-Antoine (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2022)
Curved against the hull of a peterhead (PS Guelph 2020), a slender volume of 19 poems that “wrestle with colonialism and racial violence while also reflecting a rich sensory imagery” (Partridge 2020a) was released in January 2020. By May of that year, this first book by prize-winning short-story writer, artist and spoken word poet Taqralik Partridge already figured in a list of “six Inuit literature greats” deemed essential reading. Although Partridge composed all of these poems in English, three translated versions are provided alongside their originals in curved against. The present article focuses on the two poems accompanied by Inuktitut versions, translated by Ida Saunders and Looee Arreak respectively, with a view to engaging with Partridge’s work from the perspective of eco-translation. The language related to nature – how it is employed and especially how it is translated – proves relevant to the discussion, as does the act of translation, which highlights the inter-relatedness critical to survival, literally and metaphorically speaking, for Inuit and non-Inuit alike.